2016
DOI: 10.4314/ahs.v16i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting adherence to asthma controller therapy in chest clinics in a sub-Saharan African setting: a cross-sectional study

Abstract: Abstract:Background: Adherence to controller therapy in asthma is a major concern during the management of the disease. Objective: To determine the adherence rate and identify the predictors of low adherence to asthma controller therapy. Methods: A cross-sectional study including asthma patients was conducted from November 1, 2012 to May 31, 2013 in 4 chest clinics in Cameroon. The adherence to asthma treatment was rated using Morisky Medication Adherence Scale. A multivariate logistic regression analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The study [23] is a cross sectional study that evaluated potential factors affecting adherence to asthma therapy in chest clinics in Sub-Sahara Africa. A total of 201 patients were included in the study with a mean age of 41 years that ranges between of 12-87 years of which 66% were females.…”
Section: Resultsmentioning
confidence: 99%
“…The study [23] is a cross sectional study that evaluated potential factors affecting adherence to asthma therapy in chest clinics in Sub-Sahara Africa. A total of 201 patients were included in the study with a mean age of 41 years that ranges between of 12-87 years of which 66% were females.…”
Section: Resultsmentioning
confidence: 99%
“…Participants on oral corticosteroid types of medications have better adherence than those on other types of drugs. In contrast, studies conducted in Cameroon and Ethiopia outlined no association between the types of drugs used and the level of adherence to anti-asthmatic medications [ 38 , 39 ]. This discrepancy could be related to the difference in the categories of medications taken by participants, with the current study including seven types of medications while the previously conducted studies included only three categories of anti-asthmatic medications.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, receiving anti-asthmatic medications for a longer period of time was found to be associated with poor medication adherence. According to the study conducted in Cameroon, there was no association between the duration of asthma treatment and adherence to anti-asthmatic medications [ 38 ]. This may be related to the fatigue that occurs after taking drugs for an extended period of time [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the pharmacist in asthma management is growing with time (Benavides, Rodriguez & Maniscalco-Feichtl, 2009). The visits of asthma patients to healthcare providers are also necessary to keep the disease under control and show adherence to therapy (Ngahane et al, 2016), which can be improved through shared decision-making strategies between patients and pharmacists in chronic conditions (Wilson et al, 2010).…”
Section: Zairina Et Almentioning
confidence: 99%